Misconceptions in linear algebra: the case of undergraduate students - Aygor, Nilgun; Ozdag, Hulya (ELSEVIER SCIENCE BV, 2012)
The purpose of this study was to investigate misconceptions by undergraduate students while solving matrix and determinant questions. The participants were 60 first year students from the mathematics department. The study used both qualitative and quantitative methods. The participants were asked to answer 4 questions: 2 in relation to matrices form and 2 in relation to determinants form. The data was analyzed by the researchers jointly and 6 misconceptions were revealed. (C) 2012 Published by Elsevier Ltd. Selection and/or peer review under responsibility of Prof. Dr. Huseyin Uzunboylu
Keywords: Mathematics Education; Determinants; Matrices; Linear Equations; Misconceptions; Education & Educational Research